Point-of-care testing and treatment of sexually transmitted and genital infections during pregnancy in Papua New Guinea (WANTAIM trial): protocol for an economic evaluation alongside a cluster-randomised trial - Lisa M Vallely; Peter M Siba; Rosanna W Peeling; John Kaldor; Suzanne Garland; Olga PM Saweri; David M Whiley; Stephen Rogerson; Sepehr N Tabrizi; Caroline Homer; Leanne J Robinson; Pamela J Toliman (BMJ Open)
Introduction Left untreated, sexually transmitted and genital infections (henceforth STIs) in pregnancy can lead to serious adverse outcomes for mother and child. Papua New Guinea (PNG) has among the highest prevalence of curable STIs including syphilis, chlamydia, gonorrhoea, trichomoniasis and bacterial vaginosis, and high neonatal mortality rates. Diagnosis and treatment of these STIs in PNG rely on syndromic management. Advances in STI diagnostics through point-of-care (PoC) testing using GeneXpert technology hold promise for resource-constrained countries such as PNG. This paper describes the planned economic evaluation of a cluster-randomised cross-over trial comparing antenatal PoC testing and immediate treatment of curable STIs with standard antenatal care in two provinces in PNG.Methods and analysis Cost-effectiveness of the PoC intervention compared with standard antenatal care will be assessed prospectively over the trial period (2017–2021) from societal and provider perspectives. Incremental cost-effectiveness ratios will be calculated for the primary health outcome, a composite measure of the proportion of either preterm birth and/or low birth weight; for life years saved; for disability-adjusted life years averted; and for non-health benefits (financial risk protection and improved health equity). Scenario analyses will be conducted to identify scale-up options, and budget impact analysis will be undertaken to understand short-term financial impacts of intervention adoption on the national budget. Deterministic and probabilistic sensitivity analysis will be conducted to account for uncertainty in key model inputs.Ethics and dissemination This study has ethical approval from the Institutional Review Board of the PNG Institute of Medical Research; the Medical Research Advisory Committee of the PNG National Department of Health; the Human Research Ethics Committee of the University of New South Wales; and the Research Ethics Committee of the London School of Hygiene and Tropical Medicine. Findings will be disseminated through national stakeholder meetings, conferences, peer-reviewed publications and policy briefs.Trial registration number ISRCTN37134032.